(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
P. aeruginosa is currently one of the most frequently nosocomial pathogens and the infections due to this organism are often difficult to treat due to antibiotic resistance. P. aeruginosa is an important pathogen in hospitalized patient’s causative to their morbidity and mortality due to its multiple resistance mechanisms. Therefore, as a therapeutic option becomes restricted, the search for a new agent is a priority. One hundred and fifty samples were collected from different sources, divided into two main groups: clinical (80)samples and (70) hospital environment samples as a Nosocomial, collected all from October to the December of the year 2018. All of these samples were cultured by specific and differential media, Forty (40) isolates of P.aeruginosa bacteria were identified by using microscopic examination, biochemical tests. The identification of 40 isolates of P.aeruginosa bacteria confirmed by VITEK-2 system. A molecular detection the presence of Tnp-R gene in P. aeruginosa bacteria by conventional PCR to detect the Transposons and their relationship with multiple resistance of bacteria.